2013
DOI: 10.1200/jop.2013.000882
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Virtual Multidisciplinary Lung Cancer Tumor Board in a Community Setting

Abstract: Purpose: Creating an effective platform for multidisciplinary tumor conferences can be challenging in the rural community setting. The Duke Cancer Network created an Internet-based platform for a multidisciplinary conference to enhance the care of patients with lung cancer. This conference incorporates providers from different physical locations within a rural community and affiliated providers from a university-based cancer center 2 hours away. An electronic Web conferencing tool connects providers aurally an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 11 publications
1
46
1
Order By: Relevance
“…However, the concept of the shared desktop is one of the prominent features of the Web-based tumor board, which is different from previous reports in that the images presented to the board were neither PowerPoint slideshows 11,12 nor snapshots 9 and were also different from the transmission of chest x-rays and CT scans between two hospitals. 13 The shared desktop enabled us to access in real time the original and complete images as well as any other critical information in the electronic medical records of each hospital when needed, which were unavailable by the previously reported methods.…”
Section: Discussioncontrasting
confidence: 59%
“…However, the concept of the shared desktop is one of the prominent features of the Web-based tumor board, which is different from previous reports in that the images presented to the board were neither PowerPoint slideshows 11,12 nor snapshots 9 and were also different from the transmission of chest x-rays and CT scans between two hospitals. 13 The shared desktop enabled us to access in real time the original and complete images as well as any other critical information in the electronic medical records of each hospital when needed, which were unavailable by the previously reported methods.…”
Section: Discussioncontrasting
confidence: 59%
“…These factors are interrelated, and lack of designated time has also in earlier studies been pointed out as a determinant for MDTM attendance. 1,12,[19][20][21][22] The CFIRs domain intervention includes adaption ie, to which degree the intervention can be adjusted to meet local needs, but also emphasize the importance of a balance between fulfilling the implementation and flexibility related to local needs, 18 such as adaption to different working schedules. This emphasize the need of, at an early implementation state, clarify the value of participation in MDTM to motivate health professionals in investing the time and effort needed.…”
Section: Discussionmentioning
confidence: 99%
“…31 Stevenson et al discuss the implementation of a virtual tumor board at Duke University for the treatment of their lung cancer patients, 85% of which receive their care in community cancer centers. 19 They encountered many of the same initial challenges our institution faced in establishing such a conference for telemedicine, including technological hurdles in connecting multiple cancer centers. Once the system was well established, buy-in from providers in multiple disciplines and medical centers helped bolster the conference as a staple in the treatment of their complex lung cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…16–18 Initial studies from multiple institutions have demonstrated that patient discussion in multidisciplinary video tumor boards improves patient satisfaction, provides more patients access to definitive surgical care, and does not significantly delay oncologic therapies. 16,17,19,20 However, these data are limited in an era where more and more institutions are using telemedicine to facilitate the care of these advanced stage cancer patients. 21 …”
Section: Introductionmentioning
confidence: 99%